Relationship between Thyroid Hormone Levels and Crime Type: A Controlled Study in Prisoners - Hasan Acar; Ayse Ulgen (International Journal of Endocrinology)
Various factors cause aggression, which can be related to imbalance of T3 and T4 hormones, which can act as neurotransmitters and are reported to be elevated during aggression. This indicates changes in the hypothalamic-pituitary-thyroid axis that cause long-term changes in aggressive behaviour, especially in criminals. Moreover, mental and behavioural disorders possibly occur in individuals with impairment in thyroid hormone balance. The main rationale for this study was to asses if high T3, high T4, and low TSH hormones may have an effect on aggression-related crime tendency. Furthermore, the study aimed to measure levels of thyroid hormones in prisoners and to examine relationships of the hormone levels with crime rates. Our study was conducted in Ankara Sincan Closed Prisons. The study group consisted of 208 male volunteers who were imprisoned and the control group included 82 male volunteers who were not imprisoned. Prisoners in the study group were divided into two groups: those who committed aggression-related crime (Group A, n = 96) and prisoners convicted of other crimes (Group B, n = 112). Pulse rates, T3, T4, and thyroid-stimulating hormone (TSH) levels, and theT3/T4 ratio were measured in these prisoners. Data were analysed using the Wilcoxon rank sum test and chi-square Fisher’s exact test to test for any statistically significant differences. Results showed that toxic goitre rates, T3 and T4 values, and pulse rates were significantly higher in Group A than in the control group. Significant increase in T3 and T4 levels and the presence of toxic goitre were associated with aggression-related crime. These examinations should be performed on prisoners in general, especially those convicted of violent crimes. Additional rehabilitation and research programs should also be developed for such patients.